Linear Potential Sweep Voltammetry in Conjunction with Small Amplitude Cyclic Voltammetry Study for Chalcopyrite-Xanthate Electrochemical Flotation System - Arief Sudarsono (Institute for Research and Community Services (LPPM) ITB, 1999)
Abstract. The present study was undertaken to investigate the electrochemical aspects of reactions on platinum, copper, and chalcopyrite aqueous xanthate solution interfaces by the small amplitude cyclic voltammetry (SACV) technique. In the technique, the potential of an electrode is swept linearly with time within very narrow potential limits. Typically a 10 to 20 mV peak-to-peak triangular potential excitation has been used. Characteristic parameters of the observed current-potential response loop, like apparent polarization resistance, was used to analyze the surface reaction mechanism in the flotation of chalcopyrite minerals. The analysis of the electrochemical interaction between platinum, copper and xanthate ions has also been carried out by using linear potential sweep voltammetry (LPSV) techniques in different xanthate concentrations. The voltammograms obtained on platinum appear due to the possibility of the formation of dixanthogen from the oxidation of xanthate ions, and the formation of copper-xanthate species from elecbochemical reactions between xanthate ions and copper. Studi Voltametri Penyapuan Potensial Linier Dikaitkan dengan Voltametri Siklus Amplitudo Kecil untuk Sistem Flotasi Elektrokimia Kalkopirit-xantatSari. Penelitian ini memberikan gambaran reaksi elektrokimia pada antarmuka elektroda platina, tembaga, dan kalkopirit di dalam larutan encer xantat. Penelitian dilakukan dengan metode SACV (Small Amplitude Cyclic Voltammetry), dengan rentang eksitasi potensial segitiga yang sangat kecil, yaitu 10 mV sampai 20 mV eksitasi dipakai untuk menganalisis mekanisme reaksi flotasi mineral kolkopirit. Untuk mempertegas hasil SACV penelitian dilanjutkan dengan metode LPSV (Linear Potential Sweep Voltammetry). Voltammogram yang diperoleh menggambarkan terbentuknya dixantogen di permukaan elektroda platina, dan terbentuknya senyawa tembaga-xantat karena adanya reaksi permukaan antara ion xantat dengan tembaga.